Assessing the Role of Social Media in Strengthening National Solidarity in Afghanistan: A Case Study of the Victory of Afghanistan Cricket Team - Mahdiyar, Sakhidad; YILDIZ, Göktürk (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2025)
This study investigates the impact of social media, specifically Facebook, on strengthening national solidarity in ethnically diverse Afghanistan, using the victory of the Afghanistan national cricket team as a case study. The research employs quantitative content analysis to examine Facebook users' reactions to the cricket team's success against Pakistan. Data was collected from posts on four Facebook pages representing major Afghan ethnic groups: Pashtun, Tajik, Hazara, and Uzbek. Guided by Albert Bandura's social learning theory, the analysis reveals that Facebook plays a positive role in fostering national solidarity, as evidenced by consistent support for the cricket team across all ethnic group pages. Notably, peaceful expressions of support outweighed negative comments, indicating a trend towards constructive engagement among users. This research highlights Facebook's potential as a unifying platform in Afghanistan, suggesting that it can transcend ethnic boundaries and enhance national solidarity. Future studies should explore the long-term effects of social media on national unity and consider the implications for policy-making in ethnically diverse societies.Penelitian ini menganalisis dampak media sosial, khususnya Facebook, dalam memperkuat solidaritas nasional di Afghanistan yang memiliki keragaman etnis, dengan menggunakan kemenangan tim kriket nasional Afghanistan sebagai studi kasus. Penelitian ini menggunakan analisis konten kuantitatif untuk meneliti reaksi pengguna Facebook terhadap keberhasilan tim kriket melawan Pakistan. Data dikumpulkan dari postingan di empat halaman Facebook yang mewakili kelompok etnis utama Afghanistan: Pashtun, Tajik, Hazara, dan Uzbek. Dipandu oleh teori pembelajaran sosial Albert Bandura, analisis ini mengungkapkan bahwa Facebook memainkan peran positif dalam menumbuhkan solidaritas nasional, yang dibuktikan dengan dukungan yang konsisten terhadap tim kriket di semua halaman kelompok etnis. Khususnya, ekspresi dukungan yang damai lebih banyak daripada komentar negatif, yang mengindikasikan adanya tren keterlibatan yang konstruktif di antara para pengguna. Penelitian ini menyoroti potensi Facebook sebagai platform pemersatu di Afghanistan, yang menunjukkan bahwa Facebook dapat melampaui batas-batas etnis dan meningkatkan solidaritas nasional. Penelitian di masa depan harus mengeksplorasi efek jangka panjang dari media sosial terhadap persatuan nasional dan mempertimbangkan implikasinya terhadap pembuatan kebijakan di masyarakat yang memiliki keragaman etnis.